Raising children in the Holy Quran - Alaqel, Layla Mohamed (Journal of Islamic Sciences, 2021)
The aim of the research is to explain the method of the Qur’an in raising children, by addressing the texts referring to the verses of raising children in the Holy Quran, citing some hadiths and the positions of prophets and righteous people in raising their children and the ideological, moral and emotional aspects and the rights of children over their parents in education. This research has followed the descriptive approach, and the results of the research were: God sent the prophets to guide people, and among the ways of guiding good education of children, if the Muslim child grew up healthy and correct, it was called to the goodness of the Muslim community as a word, and Islam has taken more care of the education of children than before of nations, and for the sake of raising children goodly, Islam has guaranteed children many Islamic rights, which exceed what the children’s rights organizations have adopted together, and I have recommended the importance of instilling faith in the generation. Young, as well as the interest in the educators themselves, as a large number of them do not know the Islamic curriculum in raising children, and also the work of weekly seminars extending a period of time especially for mothers, to introduce them to the importance of education and its correct methods.